Persepsi Masyarakat Aimas Unit 2 Kelurahan Malawele Dalam Menggunakan Quick Response Indonesian Standart (QRIS) Sebagai Media Transaksi - Huryatul Fiqriah (Prodi Ekonomi Syariah IAIN Sorong, 2025)
This study aims to determine public perceptions of the use of Quick Response Indonesian Standard (QRIS) as a transaction medium in Aimas Unit 2, Malawele Village. This study employed a qualitative method using a descriptive approach. Data collection was conducted through observation, interviews, and documentation. Data analysis involved data reduction, data presentation, and drawing conclusions. The researchers used triangulation to test data validity. Ten informants participated in this study. The results indicate that the Aimas Unit 2 community in Malawele Village has a positive perception of QRIS as a transaction medium. The majority of users perceived the benefits in terms of efficiency, practicality, security, ease of access, ease of learning, and understanding. This has led informants to be interested in using QRIS as a payment method today. Furthermore, the numerous payment applications connected to QRIS have also increased user interest due to perceived convenience. However, challenges remain in terms of digital literacy and equitable infrastructure availability. With broader dissemination and improved services, QRIS has great potential to become an increasingly dominant payment system in people's daily lives.